Significance of Glioma Stem-Like Cells in the Tumor Periphery That Express High Levels of CD44 in Tumor Invasion, Early Progression, and Poor Prognosis in Glioblastoma - Masahiro Nishikawa; Akihiro Inoue; Takanori Ohnishi; Shohei Kohno; Shiro Ohue; Shirabe Matsumoto; Satoshi Suehiro; Daisuke Yamashita; Saya Ozaki; Hideaki Watanabe; Hajime Yano; Hisaaki Takahashi; et al. (Stem Cells International)
Glioblastoma multiforme (GBM) is the most aggressive malignant brain tumor and a subpopulation of glioma stem-like cells (GSCs) is likely responsible for the invariable recurrence following maximum resection and chemoradiotherapy. As most GSCs that are located in the perivascular and perinecrotic niches should be removed during tumor resection, it is very important to know where surviving GSCs are localized. Here, we investigated the existence and functions of GSCs in the tumor periphery, which is considered to constitute the invasion niche for GSCs in GBM, by analyzing expression of stem cell markers and stem cell-related molecules and measuring particular activities of cultured GSCs. In addition, the relationship between GSCs expressing particular stem cell markers and pathological features on MRI and prognosis in GBM patients was analyzed. We showed that GSCs that express high levels of CD44 are present in the tumor periphery. We also found that vascular endothelial growth factor (VEGF) is characteristically expressed at a high level in the tumor periphery. Cultured GSCs obtained from the tumor periphery were highly invasive and have enhanced migration phenotype, both of which were markedly inhibited by CD44 knockdown. Higher expression of CD44 in the tumor periphery than in the core was correlated with a highly invasive feature on MRI and was associated with early tumor progression and worse survival, whereas lower expression of CD44 in the tumor periphery corresponded to low invasion and was associated with longer survival. The low invasion type on MRI tended to show high levels of VEGF expression in the tumor periphery, thus presenting the tumor with high proliferative activity. These results imply the significance of GSCs with high levels of CD44 expression in the tumor periphery compared to the core, not only in tumor invasion but also rapid tumor progression and short survival in patients with GBM.